Indigenous peoples and demography : the complex relation between identity and statistics - Axelsson, Per, 1972-; Sköld, Peter (Berghahn Books, 2011)
When researchers want to study Indigenous populations they are dependent upon the highly variable way in which states or territories enumerate, categorize, and differentiate Indigenous people. In this volume, anthropologists, historians, demographers, and sociologists have come together for the first time to examine the historical and contemporary construct of Indigenous people in a number of fascinating geographical contexts around the world, including Canada, the United States, Colombia, Russia, Scandinavia, the Balkans, and the United Kingdom. Using historical and demographical evidence, the contributors explore the creation and validity of categories for enumerating Indigenous populations; the use and misuse of ethnic markers, micro-demographic investigations, and demographic databases; and thereby show how the situation varies substantially between countries.